STATE OF THE ART OF DISSERTATION PRODUCTIONS IN THE PROFESSIONAL MASTER’S PROGRAM IN MATHEMATICS IN THE NATIONAL NETWORK THAT DEALS WITH TEACHER TRAINING, FROM 2012 ONWARDS - Lago, Willanickson Jacksemuller Santos; Cartágenes, Eric Sousa (Revista Sistemática, 2024)
This work seeks to show the production of works with a theme in mathematics education in the Professional Master’s program in Mathematics in the National Network that deal with teacher training, from 2012 onwards. In the construction of the scenario of this research, we collected data through the keywords Teacher Training and Continuing Education on the PROFMAT Portal. After the survey of the dissertations, the distribution and comparison by regions of the country was made, and an analysis of the current situation of these productions within this program was made. In this work, we present the difficulty of the program in enabling the production of research on the theme of teacher training and the rigid line of research present in the Professional Master’s Degree in Mathematics in the National Network – PROFMAT.